Contributions to the knowledge of the biodiversity of Heteroptera (Insecta) in the Southern Cone, Argentina - Pall, José Luis; Coscarón, María Del Carmen (Zootaxa, 2016)
Insect studies for different regions are scarce as most of the material is collected in isolation, thus preventing extensive taxonomic listings. Conducting inventories of terrestrial biodiversity in a specific area is an arduous task, with many obstacles: mainly the lack of data on taxonomic and geographical distribution necessary to study them. The aim of this work is to present new contributions to the geographical distribution of Heteroptera in the Pampean, Espinal and Monte phytogeographic provinces, in the central region of Argentina, Southern Cone. Ten samples were taken, using the following methods, beating sheet, light trap and G-Vac (garden-vacuum). Each point within the site was sampled by each type of trap for one minute, leading to a total of 10 minutes per capture method in each site, except the light tramp. Twenty-two species are recorded for the first time in the central region of Argentina, Southern Cone.